2022
DOI: 10.3390/cancers14030641
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of DNA Damage Response by SAM and HD Domain Containing Deoxynucleoside Triphosphate Triphosphohydrolase (SAMHD1) Determines Prognosis and Treatment Efficacy in Different Solid Tumor Types

Abstract: SAMHD1 is a deoxynucleotide triphosphate (dNTP) triphosphohydrolase with important roles in the control of cell proliferation and apoptosis, either through the regulation of intracellular dNTPs levels or the modulation of the DNA damage response. However, SAMHD1′s role in cancer evolution is still unknown. We performed the first in-depth study of SAMHD1′s role in advanced solid tumors, by analyzing samples of 128 patients treated with chemotherapy agents based on platinum derivatives and/or antimetabolites, de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 59 publications
3
20
0
Order By: Relevance
“…In the colorectal cancer, high expression SAMHD1 correlated with metastasis [ 30 ] and indicated poor prognosis of stage II patients [ 31 ]. Consistent with our results, Eudald Felip et al found that low expression of SAMHD1 was associated with a positive prognosis in breast, ovarian and non-small cell lung cancer patients [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the colorectal cancer, high expression SAMHD1 correlated with metastasis [ 30 ] and indicated poor prognosis of stage II patients [ 31 ]. Consistent with our results, Eudald Felip et al found that low expression of SAMHD1 was associated with a positive prognosis in breast, ovarian and non-small cell lung cancer patients [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…In view of these findings, the role of SAMHD1 was also evaluated in a cohort of 22 ovarian cancer patients, previously described (11).…”
Section: Resultsmentioning
confidence: 99%
“…T47D cells were obtained from Sigma-Aldrich-ECACC (European Collection of Authenticated cell cultures, 85102201-1VL) and grown in complete Dulbecco’s modified Eagle’s medium (DMEM, ThermoFischer) supplemented with 10% of heat-inactivated fetal bovine serum (FBS, ThermoFisher) and antibiotics 100 U/ml penicillin, 100 μg/ml streptomycin (Life Technologies) and maintained at 37°C in a 5% CO 2 incubator. For generation of knock-out (KO) cells, T47D cells were transfected with a plasmid expressing a CRISPR-Cas9 construct designed to disrupt the sequence corresponding to exon 5 of SAMHD1 gene that encodes for HD domain (CRISPR-SAMHD1), as described previously ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IHC was performed routinely on all primary colon cancer samples, as previously described ( 26 , 27 ). All samples were fixed in 10% neutral buffered formalin at room temperature for 1 h and maintained at 4°C with 30% saccharose overnight.…”
Section: Methodsmentioning
confidence: 99%